POPULATION STRUCTURE OF THE Meretrix meretrix IN THE INTERTIDAL ZONE OF SRI TANJUNG VILLAGE RUPAT SUB-DISTRICT BENGKALIS DISTRICT - Khoiriyah, Latifatul; Tanjung, Afrizal; Elizal, Elizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
This study aims to determine the population structure of Meretrix meretrix in the intertidal zone in Sri Tanjung Village, including abundance, distribution patterns, and size distribution. This research was conducted in February 2024 in Sri Tanjung Village, Rupat District, Bengkalis Regency. The research method used was the survey method. M. meretrix is one of the biota that lives in tidal areas where the subzone that experiences tides is divided into 3 (three) subzones (upper, middle, and lower). The research site is divided into two research stations. Each station is divided into 3 (three) transects, each consisting of 3 (three) plots with a size of 1 x 1 m². Environmental parameters include temperature, salinity, pH, substrate type, and organic matter. The results showed that the highest abundance was found in the Lower subzone at station I, with an average abundance of 8.66 ind/m2, and at station II, with an average abundance of 4.33 ind/m2. In comparison, the lowest abundance is found in the upper subzone at station I with an average value of 3 ind/m2, and the lowest abundance at station II with an average of 1 ind/m2. The size distribution of M. meretrix at station 1 obtained seven classes, with the highest number of individuals in the 3rd class (2.33 - 2.92 cm), while at station 2, there were six classes where the highest number of individuals was in the 3rd class (1.47 - 1.81 cm). The distribution pattern of M. meretrix found is random and uniform. The analysis results of M. meretrix abundance between stations and M. meretrix abundance between intertidal subzones differed significantly.